Influence of Telecommuting on Work-life Balance and Employee Happiness: An Empirical Study of Sri Lankan Employees - Uresha , K. I. (International Journal of Management Excellence (ISSN: 2292-1648), 2020)
- Telecommuting, work-life balance and employee happiness are three most compelling concepts in the present corporate world which aid to optimize employee performance and gain strategic competitive edge. Recognizing the significance of these factors to the real world of work, a systematic empirical endeavor made to address the existing research niche and intellectual curiosity of the author by examining the relationship between telecommuting and work-life balance and telecommuting and employee happiness and the impact of telecommuting on work-life balance and employee happiness in Sri Lankan context. Hence, present study contributes to the literature in the areas of telecommuting, work-life balance and employee happiness. The study is an analytical study where the time horizon was cross sectional and unit of analysis is individual employees. Survey method was adopted using an author developed questionnaire consisting of three instruments to gather data and 110 employees were responded utilizing convenient sampling technique. Reliability and validity of the instruments were assured. Empirical findings of the study reveal that there is a significant positive relationship between telecommuting and work-life balance, there is a significant positive relationship between telecommuting and employee happiness as well as telecommuting has a significant positive impact jointly on work-life balance and employee happiness in Sri Lankan context